Circumferential Expansion Property of Composite Wrapping System for Main Cable Protection of Suspension Bridge - Pengfei Cao; Hai Fang; Weiqing Liu; Yong Zhuang; Yuan Fang; Chenglin Li (Advances in Polymer Technology)
A composite wrapping system for main cable protection of suspension bridges was designed by using prepreg fiber-reinforced composites and nitrile rubber. The circumferential expansion performance of the system was tested, and the curves of circumferential bearing capacity and radial displacement of the components were obtained. Failure modes of each group of components were compared and analyzed. The results show that most of the components are vertically fractured at the lap transition. The increase of the number of prepreg layers contributed the most to the circumferential bearing capacity of components, with a growth rate of 65.31%~109.01%. The increase of rubber belt layers had the most significant effect on the radial displacement of the components, with a growth rate of 7.06%~23.5%. In the initial stage of the test, the strain of each part of the component was smaller due to the compaction by the loading device, and the strain value of the component was generally linearly increased during the loading process, during which the strain of the overlap was the smallest. The calculated cross-sectional temperature deformation of the main cable is in good agreement with the experimental data. The application of the rubber belt increases the deformation of the main cable; therefore, the protection system for the main cable could have more deformation redundancy and delay the arrival of the ultimate strain of the outer prepreg wrap.